2010
DOI: 10.1007/s11705-009-0291-5
|View full text |Cite
|
Sign up to set email alerts
|

Developing macromolecular therapeutics: the future drug-of-choice

Abstract: Macromolecular drugs including peptides, proteins, antibodies, polysaccharides and nucleic acids have been widely used for therapy of major diseases such as carcinoma and AIDS as well as cardiovascular and neurodegenerative disorders among other medical conditions. Due to their unmatched properties of high selectivity and efficiency, macromolecular drugs have been recognized as the drug-of-choice of the future. Since worldwide progress on macromolecular therapeutics still remains in the infant stage and is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Subsequently, various classes of CPPs, including arginine/lysine-rich cationic peptides, LMWP, Penetratin and VP22 [15,24,31,32,33,34], as well as amphipathic peptides such as MAP, MPG, pep-1, etc., were also reported and utilized in either remarkable intracellular delivery strategies or the successful application in medical and biological field [17,19,25,26,27,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. Via covalent linkage or non-covalent charge-associated aggregation, linkage, both in vitro and in vivo results demonstrated that CPPs could assist the delivery of virtually all types of molecular cargos including proteins [2,16,20,26,46,49,50,51,52,53,54,55], nucleic acids [33,35,36,56,57,58,59,60], and nano-carriers such as magnetic iron oxide nanoparticles (MION) [61,62,63,64,65,66,67,68] into cells.…”
Section: Cell Penetrating Peptides (Cpps)-assisted Strategies For mentioning
confidence: 99%
“…Subsequently, various classes of CPPs, including arginine/lysine-rich cationic peptides, LMWP, Penetratin and VP22 [15,24,31,32,33,34], as well as amphipathic peptides such as MAP, MPG, pep-1, etc., were also reported and utilized in either remarkable intracellular delivery strategies or the successful application in medical and biological field [17,19,25,26,27,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. Via covalent linkage or non-covalent charge-associated aggregation, linkage, both in vitro and in vivo results demonstrated that CPPs could assist the delivery of virtually all types of molecular cargos including proteins [2,16,20,26,46,49,50,51,52,53,54,55], nucleic acids [33,35,36,56,57,58,59,60], and nano-carriers such as magnetic iron oxide nanoparticles (MION) [61,62,63,64,65,66,67,68] into cells.…”
Section: Cell Penetrating Peptides (Cpps)-assisted Strategies For mentioning
confidence: 99%